A Research on Bipolar Valued Vague Normal Subrings of A Ring - k.Arjunan, b.Deeba, s. Naganathan (Mathematical Statistician and Engineering Applications, 2023)
In this paper, bipolar valued vague normal subring of a ring is introduced and some properties are discussed. bipolar valued vague normal subring of a ring is a generalized form of vague normal subring of the ring, vague normal subring of the ring is a generalized form of fuzzy normal subring of the ring and fuzzy normal subring of the ring is a generalized form of ring.